The influencing pathway of agrivoltaics on soybean protein concentration - Hu, Yuru; Zhang, Xueyan; Ma, Xin (Frontiers in Plant Science, 2025)
Agrivoltaics has the potential to enable simultaneous energy and food production. However, its impact on crop quality and the underlying mechanisms remain insufficiently understood, which poses a significant challenge to the development of agrivoltaic systems. This study aims to investigate the process and pathways through which agrivoltaic systems influence soybean protein concentration by examining crop responses to three types of photovoltaic structures: traditional photovoltaic panels, checkerboard photovoltaic panels, and translucent photovoltaic panels. The results indicate that: 1) soybeans grown under translucent photovoltaic panels exhibited no significant decrease in nitrogen accumulation or crude protein concentration compared to the control group; 2) logistic model analysis revealed that translucent photovoltaic panels outperformed traditional panels in terms of maximum nitrogen accumulation potential and the timing of peak accumulation, highlighting their relative advantage in preserving soybean protein concentration; 3) the effect of agrivoltaics on grain protein concentration is multifaceted, primarily involving nitrogen accumulation in leaves prior to the grain-filling stage and nitrogen translocation during the grain-filling stage. These findings provide robust empirical evidence and a theoretical framework for understanding how photovoltaic systems affect soybean quality and for developing strategies to mitigate any decline in quality. This research contributes to the future promotion and adoption of agrivoltaic systems.